2018
DOI: 10.3389/fimmu.2018.01088
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant T Cell Signaling and Subsets in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic multi-organ debilitating autoimmune disease, which mainly afflicts women in the reproductive years. A complex interaction of genetics, environmental factors and hormones result in the breakdown of immune tolerance to “self” leading to damage and destruction of multiple organs, such as the skin, joints, kidneys, heart and brain. Both innate and adaptive immune systems are critically involved in the misguided immune response against self-antigens. Dendritic cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
144
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 241 publications
(244 reference statements)
2
144
0
2
Order By: Relevance
“…While the exact molecular mechanisms of how female hormones regulate the immune system are yet incompletely elucidated, studies show that they control development, homeostasis, gene expression, and signaling processes in T and B lymphocytes to influence their function in health and disease. This review focuses on the role of sex hormones on the adaptive immune system and in autoimmune diseases with a focus on the prototype systemic autoimmune disease SLE ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…While the exact molecular mechanisms of how female hormones regulate the immune system are yet incompletely elucidated, studies show that they control development, homeostasis, gene expression, and signaling processes in T and B lymphocytes to influence their function in health and disease. This review focuses on the role of sex hormones on the adaptive immune system and in autoimmune diseases with a focus on the prototype systemic autoimmune disease SLE ( 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Belimumab, which inhibits the B cell activating factor (BAFF), a key survival cytokine for B cells, is currently the only approved biological agent for SLE [12]. However, the efficacy of drugs targeting B cells is limited, and other approaches, including those targeting T cells, are required to improve treatment options for SLE patients [13,14]. S1P 1 receptor modulators suppress infiltration of autoreactive T cells into sites of inflammation by inhibiting lymphocyte egress from secondary lymphoid organs [15] and have proven their therapeutic potential in RRMS and ulcerative colitis [3,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…We reported significant increased biological functions in CD80®CD28 and CD86®CD28 ( Figure 4C) for the first time, which activate TCR singling pathway following MHCII antigen presentation and finally result in growing up the differentiation and proliferation rate of T cells in response to the apoptotic autoantigens. Recently, Katsuyama et al indicated a T cells hyperresponsiveness following abnormal TCR signaling pathway in SLE patients [12]. At the end of the SLE signaling pathway, end-organ damage reported via several key genes (FCGR1A, C3, C7, C8G and C9).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, genome-wide association studies (GWAS) coupled with gene expression profiling data shed light on the critical role regarding the dysregulation of genes involved in B-cell receptor (BCR) and T-cell receptor (TCR) mediated signaling in B cells and T cells of SLE patients, respectively [7]. As a validation, an aberrant TCR signaling followed by hyperresponsiveness of T cells has been shown in patients with SLE [12]. Despite numerous strongminded studies that have been done, the pathogenesis is still far from clear.…”
Section: Introductionmentioning
confidence: 99%